Christian Bobin: The Ruins of Heaven - Sanz Barajas, Jorge (Razón y fe, 2018)
Edit. Sibirana, Zaragoza 2012, 134 pp., ISBN 978-84-939600-3-2 Translation by Andrés García Inda and María José González Ordovás